2016
DOI: 10.3892/ijo.2016.3444
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sulforaphane on the cell cycle, apoptosis and expression of cyclin D1 and p21 in the A549 non-small cell lung cancer cell line

Abstract: Sulforaphane (SFN) is present in plants belonging to Cruciferae family and was first isolated from broccoli sprouts. Chemotherapeutic and anticarcinogenic properties of sulforaphane were demonstrated, however, the underlying mechanisms are not fully understood. In this study we evaluated the expression of cyclin D1 and p21 protein in SFN-treated A549 cells and correlated these results with the extent of cell death and/or cell cycle alterations, as well as determined a potential contribution of cyclin D1 to cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 41 publications
(37 reference statements)
2
23
0
Order By: Relevance
“…It is possible that cyclin D1 overexpression in the H1299 cell line is responsible for moderate response to drug intervention. Our previous study showed that cyclin D1 overexpression in the A549 cell line prevented SFN-induced apoptosis (43). Moreover, we also observed an increase in cyclin D1 after treatment with the lowest dose of SFN (30 µM).…”
Section: Discussionsupporting
confidence: 66%
“…It is possible that cyclin D1 overexpression in the H1299 cell line is responsible for moderate response to drug intervention. Our previous study showed that cyclin D1 overexpression in the A549 cell line prevented SFN-induced apoptosis (43). Moreover, we also observed an increase in cyclin D1 after treatment with the lowest dose of SFN (30 µM).…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies also demonstrated that Sul could induce G2/M arrest by inactivation of the Cyclin B1 and Cdc2 complex without altering expression level of Cyclin B1 in ovarian cancer cells [35] and with increased protein expression of Cyclin B1 in acute lymphoblastic leukemia cells [36]. Sul increased Cyclin D1 protein expression when it induced G2/M arrest, and Cyclin D1 overexpression has been reported to be required for Sul-induced apoptotic and necrotic cell death in non-small lung cancer cells [34]. Although exact mechanisms involved still need to be elucidated, this study clearly demonstrated that the anti-cancer mechanisms of Cur are quite different from those of Sul.…”
Section: Resultsmentioning
confidence: 90%
“…In these studies that demonstrated induction of apoptosis by Sul, relatively high concentrations of Sul were used such as 20 μM in PC-3 cells [32] and 30 μM in Jurkat T leukemia cells [33]. In addition, cell death induced by Sul appeared to be mainly by necrosis with only a small amount of apoptosis [34]. Therefore, treatment with antioxidants at the hMED and the MED induced anti-proliferative pathways in accordance with their growth inhibitory effects (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclins, cyclin-dependent kinases (CDKs) and various kinds of cyclin-dependent kinase inhibitors (CDKIs) are closely involved in cell cycle distribution [13]. Cyclin D1, which is responsible for the transition from G1 phase to S phase via forming complexes with CDK4 and CDK6, is one of the most important cell cycle regulators in the process of tumor development [14, 15]. M. S. Lima et al reported that Cyclin D1 was overexpressed in RCC and can be used as an prognostic factor in RCC patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…M. S. Lima et al reported that Cyclin D1 was overexpressed in RCC and can be used as an prognostic factor in RCC patients [16]. P21 protein is a well-known CDK inhibitor, participating in cell-cycle regulation via the inhibition of cyclin-CDK complex activity in G1 phase [15]. Tumor suppressor p53 also takes part in regulating the cell cycle process and p21 acts as a major downstream effector of p53 in G1 phase [17, 18].…”
Section: Introductionmentioning
confidence: 99%